Carers, ethics and dementia: a survey and review of the literature. - Hughes, J; Hope, T; Savulescu, J; Ziebland, S (2002)
BACKGROUND: Much has been written on ethical issues in dementia, but usually from the point of view of the various professionals involved. Whilst there has been an increasing amount of interest in the psychosocial problems that face the carers of people with dementia, the ethical nature of some of these problems has largely been ignored. OBJECTIVE: To review the literature on ethical issues in dementia from the perspective of the main, non-professional carers of people with dementia. METHOD: A systematic literature search using Medline, Clinpsych and CINAHL databases between 1982 and 2000. A pilot study of carers. RESULTS: The lay perspective provides both a wide variety of issues and unique approaches. Although in the literature quantitative research answers some questions, it is qualitative research that deepens our understanding of the issues from the perspective of carers. CONCLUSION: It is particularly qualitative research that brings out the ethical issues for carers, which tend to be more varied than the ethical issues raised in the professional literature. Awareness of such issues could inform and shape the support given to carers.